Controllable and green synthesis of robust graphene aerogels with tunable surface properties for oil and dye adsorption. (14th December 2017) - Qiu, Lijuan; Wan, Wenchao; Tong, Zhongqiu; Zhang, Ruiyang; Li, Lina; Zhou, Ying
Abstract : Robust graphene aerogels with tunable surface properties are hydrothermally prepared using vitamin C at different pHs for oil and dye adsorption. Abstract : Recently, graphene aerogels (GAs) with abundant pores, ultra-light density and excellent adsorption capacity have been regarded as promising high efficiency oil/water and dye/water separation materials and attracted much attention for water remediation. However, the green and controllable synthesis of GAs with tunable surface properties and high mechanical strength remains a challenge. In this work, we develop a facile hydrothermal method using vitamin C (VC) as a green reducing agent. It is found that VC ensures high mechanical strength while the surface hydrophobicity can be easily controlled at different pH values. The hydrophobic and robust GA obtained at pH 5 demonstrates outstanding oil–water separation capabilities in both non-turbulent and turbulent oil–water mixtures under continuous adsorption, whereas the hydrophilic GA obtained at pH 11 shows excellent dye–water separation performance. This artificial controllable strategy for the modification of GAs with expected properties paves a promising route to develop GAs for various applications.